Reseña de Casas Gómez, Miguel (dir.) & Fernández Smith, Gérard (ed.) (2005). IX Jornadas de Lingüística - Rodríguez-Piñero Alcala, Ana Isabel (Pragmalingüística, 2008)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Casas Gómez, Miguel (dir.) & Fernández Smith, Gérard (ed.) (2005). IX Jornadas de Lingüística.